2007
DOI: 10.1152/ajpheart.00965.2006
|View full text |Cite
|
Sign up to set email alerts
|

ANG II type 1 receptor antagonist irbesartan inhibits coronary angiogenesis stimulated by chronic intermittent hypoxia in neonatal rats

Abstract: Rakusan K, Chvojkova Z, Oliviero P, Ostadalova I, Kolar F, Chassagne C, Samuel JL, Ostadal B. ANG II type 1 receptor antagonist irbesartan inhibits coronary angiogenesis stimulated by chronic intermittent hypoxia in neonatal rats. Am J Physiol Heart Circ Physiol 292: H1237-H1244, 2007. First published December 1, 2006; doi:10.1152/ajpheart.00965.2006.-Chronic hypoxia has been shown to stimulate myocardial microvascular growth and improve cardiac ischemic tolerance in young and adult rats. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Instead, the PI3K/Akt pathway was suggested to be involved in IH-induced cardioprotection in this study. Similarly, Rakusan et al (48) reported VEGF-independent vascularization and cardioprotection induced by IH with the involvement of caveolin-1 and a receptor of angiotensin.…”
Section: Discussionmentioning
confidence: 86%
“…Instead, the PI3K/Akt pathway was suggested to be involved in IH-induced cardioprotection in this study. Similarly, Rakusan et al (48) reported VEGF-independent vascularization and cardioprotection induced by IH with the involvement of caveolin-1 and a receptor of angiotensin.…”
Section: Discussionmentioning
confidence: 86%
“…It has been previously reported that the high oxidative stress produced in EAC model causing chronic hypoxia and tissue injury [18], [33]. This chronic hypoxia increased the density of angiotensin II type 1receptors [34]. Therefore, EAC model can be considered as a good target for angiotensin II type 1 receptor blockers.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, EAC model can be considered as a good target for angiotensin II type 1 receptor blockers. Angiotensin II type 1 receptor blockade is reported to have inhibitory effects on many models of angiogenesis 3437 and on the growth of microvessels induced by angiotensin II[38].Therefore, angiotensin II type 1 receptor blockers have been considered as an anti-angiogenic therapeutic option [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sasaki et al (2000) demonstrated that exposure of myocytes to an NO donor directly activates mitochondrial K ATP channels. Furthermore, Rakusan et al (2007) have observed that angiotensin II is also involved in the mechanisms of adaptation of the immature heart to CH: the chronic blockade of angiotensin II type 1 receptors by irbesartan surprisingly, in contrast to adults, completely abolished the cardioprotective effect of CH. These observations should be taken into consideration in the treatment of children suffering from cyanotic congenital heart disease.…”
Section: Cardiac Protection Of the Immature Heartmentioning
confidence: 99%